Strategi Komunikasi Wanita dalam Film Barbie - Sitinjak, Vivi Novalia; S. Meliala, Grace Cya Aprilia; Sihombing, Riska Wati; Simamora, Maria Yosepine (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study, conducted in a sociolinguistic setting, looks into the communication strategies utilized by female characters in the animated film